Geschlechtertypisierungen im Kontext von Familie und Schule - Andresen, Sabine; Barbara, Rendtorff; Andresen, Sabine; Barbara, Rendtorff (Leverkusen-Opladen Verlag Barbara Budrich, 2006)
The yearbook 2006 deals with gender images and gender-typical expectations with which children, adolescents and young adults are confronted in the process of growing up. In addition, new perspectives on gender relations in the family are discussed.
German
Keywords: Gender studies, gender groups; gender studies; family; school; growing up; culture; history; gender roles; Geschlechterforschung; Familie; Schule; Aufwachsen; Kultur; Geschichte; Erinnerung